MicroRNA-874-3p Aggravates Doxorubicin-Induced Renal Podocyte Injury via Targeting Methionine Sulfoxide Reductase B3. (18th August 2020) - Dai, Yan; Gao, Meng; Li, Linxia; Mao, Zhang; Xu, Lina; Yin, Lianhong; Qi, Yan; Peng, Jinyong
Abstract : Clinical application of doxorubicin (Dox) is limited due to its serious side effects including nephrotoxicity, and kidney podocytes play important roles in renal diseases. MicroRNAs (miRNAs) are critical regulators associated with human diseases. The purpose of this study was to explore a novel target in adjusting Dox-induced renal podocyte injury. Through a double luciferase reporter gene experiment, it was found that miR-874-3p directly targeted methionine sulfoxide reductase B3 (MsrB3). During the tests of miR-874-3p inhibitor and MsrB3 siRNA in human podocytes or miR-874-3p antagomir in mice, we found that the expression levels of downstream oxidative stress and apoptosis-related proteins were regulated by miR-874-3p/MsrB3 signal to alleviate or aggravate renal podocyte injury. The data in the present work showed that miR-874-3p aggravated Dox-caused renal podocyte injury by promoting apoptosis and oxidative damage via inhibiting MsrB3. Therefore, miR-874-3p/MsrB3 should be considered as a new therapeutic target in controlling renal podocyte injury induced by Dox.